2004
DOI: 10.1016/j.molcel.2004.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Selective Regulation of Vitamin D Receptor-Responsive Genes by TFIIH

Abstract: Mutations in the XPD subunit of the transcription/repair factor TFIIH cause the Xeroderma pigmentosum disorder. We show that in some XP-D deficient cells, transactivation by the vitamin D receptor (VDR) is selectively inhibited for a subset of responsive genes, such as CYP24, and that the XPD/R683W mutation prevents VDR recruitment on its promoter. Contrary to other nuclear receptors, VDR, which lacks a functional A/B domain, is not phosphorylated and consequently not regulated by the cdk7 kinase of TFIIH. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 47 publications
2
50
0
1
Order By: Relevance
“…The recent discovered differential phosphorylation of the XPB subunit of TFIIH after UV [48], suggests an active switch between the function of TFIIH in repair and transcription. Recently, the multifunctionality of TFIIH has been complemented with documented involvements in activated RNA polymerase II transcription [49] and [50], in basal transcription initiation of rRNA genes by RNA polymerase I [51] and [52] and a possible role of the CAK subcomplex in cell cycle [47] and [53]. The ERCC1/XPF complex is a NER factor with engagements in interstrand cross-link repair, since deficiency for this structure-specific endonuclease causes sensitivity for cross-linking agents.…”
Section: Involvement Of Ner Factors In Other (Dna Repair) Processesmentioning
confidence: 99%
“…The recent discovered differential phosphorylation of the XPB subunit of TFIIH after UV [48], suggests an active switch between the function of TFIIH in repair and transcription. Recently, the multifunctionality of TFIIH has been complemented with documented involvements in activated RNA polymerase II transcription [49] and [50], in basal transcription initiation of rRNA genes by RNA polymerase I [51] and [52] and a possible role of the CAK subcomplex in cell cycle [47] and [53]. The ERCC1/XPF complex is a NER factor with engagements in interstrand cross-link repair, since deficiency for this structure-specific endonuclease causes sensitivity for cross-linking agents.…”
Section: Involvement Of Ner Factors In Other (Dna Repair) Processesmentioning
confidence: 99%
“…All of the mutations associated with TTD result in reduced cellular levels (8,9) and impaired functioning of TFIIH in NER and basal transcription (10)(11)(12). Furthermore, they may interfere with the role of TFIIH in transcription regulation (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Furthermore, XPG was recently identified as a protein required for maintaining the integrity of the TFIIH complex, and therefore also engaged in the transcription process (20). Even though the contribution of the DNA repair deficiency to the clinical features of patients with XP, CS, or XP/ CS is irrefutable, studies have shown a clear dysregulation of a variety of transcriptional pathways, which may also contribute to the clinical phenotype of these patients (21)(22)(23)(24)(25)(26)(27). Interestingly, at the cellular level, XP/CS cells share with CS cells a sustained global transcriptional arrest after UV irradiation, which has been always explained by the inability of these cells to perform TCR (17,28).…”
mentioning
confidence: 99%